Financial Risk Management in Enterprises (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In modern conditions, of particular interest are the fundamentally new possibilities of financial analysis, in which financial risk assessment is an important part of financial management. One of the main aspects of assessing financial risks is the choice of an appropriate methodology for assessing the degree of a specific type of risk, which predetermines the correctness of analytical calculations to determine the degree of riskiness of transactions. In this regard, the article discusses methods of financial risk management, as well as the possibilities of their application in modern economic conditions.